2005
DOI: 10.1111/j.1551-2916.2005.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of AlN Nanopowder from γ‐Al2O3by Reduction–Nitridation in a Mixture of NH3–C3H8

Abstract: Aluminum nitride (AlN) powders were synthesized by gas reduction–nitridation of γ‐Al2O3 using NH3 and C3H8 as the reactant gases. AlN was identified in the products synthesized at 1100°–1400°C for 120 min in the NH3–C3H8 gas flow confirming that AlN can be formed by the gas reduction–nitridation of γ‐Al2O3. The products synthesized at 1100°C for 120 min contained unreacted γ‐Al2O3. The 27A1 MAS NMR spectra show that Al–N bonding in the product increases with increasing reaction temperature, the tetrahedral AlO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 46 publications
(48 reference statements)
3
29
0
Order By: Relevance
“…Yamakawa et al also synthesized AlN at 1200°C, but they used NH 3 -C 3 H 8 as the reactant gas. 19 Our results suggest that microwaves enhanced the CRN reaction without using a reactive gas such as NH 3 -C 3 H 8 , and microwave irradiation enabled us to synthesize single-phase AlN at temperatures above 1200°C.…”
Section: Resultsmentioning
confidence: 76%
“…Yamakawa et al also synthesized AlN at 1200°C, but they used NH 3 -C 3 H 8 as the reactant gas. 19 Our results suggest that microwaves enhanced the CRN reaction without using a reactive gas such as NH 3 -C 3 H 8 , and microwave irradiation enabled us to synthesize single-phase AlN at temperatures above 1200°C.…”
Section: Resultsmentioning
confidence: 76%
“…The main alumina phase of (c), (d), (e), and (f) was h-Al 2 O 3 (Fig. In addition, Yamakawa et al reported 15 According to these reports, c-Al 2 O 3 is more easily nitrided than d-, h-, or a-Al 2 O 3 . On the other hand, (a), (b), and (g) had only the c, d, and a-Al 2 O 3 phases, respectively.…”
Section: ) Synthesis Of Aln From Powders Containing Different Aluminmentioning
confidence: 93%
“…Figure 3 shows that nitridation ratios for (c)', (d)', (e)', and (f)' were higher than those of (a)', (b)' and (g)'. 15 These earlier works have suggested that a-Al 2 O 3 , which has only octahedral AlO 6 sites, is less readily nitrided than transition alumina. The main alumina phase of (c), (d), (e), and (f) was h-Al 2 O 3 (Fig.…”
Section: ) Synthesis Of Aln From Powders Containing Different Aluminmentioning
confidence: 99%
“…It is a promising advanced ceramic material with many excellent properties such as high band gap of around 6.2 eV, high electrical resistivity (10 13 ), small dielectric constant (8.8 at 1 MHz), and low thermal expansion coefficient (which closely matched that of silicon, 4.7×10 −6 K −1 ) [1,2]. Many methods have been reported on the production of AlN powders including direct nitridation of Al metal in N 2 or NH 3 atmosphere, carbothemal reduction of Al 2 O 3 in Al 2 O 3 -C-N 2 system or Al 2 O 3 -NH 3 -C 3 H 8 system [3][4][5], vapor phase synthesis [6,7], plasma synthesis [8,9], and self-propagating high temperature synthesis [10,11]. Among them, two primary processes to manufacture AlN powders commercially are direct nitridation and carbothermal reduction [12].…”
Section: Introductionmentioning
confidence: 99%